Pengaruh Religuisitas, Pembiayaan dan Pemberdayaan Terhadap Perkembangan UMKM di Kota Medan - Sri Rezeki Nur Hadiati Putri Sinaga; Sugianto Sugianto; Muhammad Arif (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the influence of the variables of religiosity, financing and empowerment on the development of MSMEs. This research is a quantitative research with multiple linear regression model with the help of SPSS version 23 program. The population in this study amounted to 1413 respondents. By using a random sampling technique, a sample of 90 respondents was taken. The results of this study found that religiosity had no significant effect on the development of MSMEs. Taken together, religiosity, financing and empowerment can significantly influence the MSME Development variable. Based on the R square value, it shows that the variables of religiosity, financing and empowerment have an effect on the development of MSMEs by 67.8% and the rest because 32.2% has no effect. Keywords: Religiosity, Financing, Empowerment, MSME Development